Protocol for outcome reporting and follow-up in the Targeted Hypothermia versus Targeted Normothermia after Out-of-Hospital Cardiac Arrest trial (TTM2) - Lilja, Gisela; Nielsen, Niklas; Ullén, Susann; Blennow Nordstrom, Erik; Dankiewicz, Josef; Friberg, Hans; Heimburg, Katarina; Jakobsen, Janus Christian; Levin, Helena; Callaway, Clifton; Cariou, Alain; Eastwood, Glenn M; et al. (Resuscitation, 2020)
AIMS: The TTM2-trial is a multi-centre randomised clinical trial where targeted temperature management (TTM) at 33 °C will be compared with normothermia and early treatment of fever (≥37.8 °C) after Out-of-Hospital Cardiac Arrest (OHCA). This paper presents the design and rationale of the TTM2-trial follow-up, where information on secondary and exploratory outcomes will be collected. We also present the explorative outcome analyses which will focus on neurocognitive function and societal participation in OHCA-survivors. METHODS: Blinded outcome-assessors will perform follow-up at 30-days after the OHCA with a telephone interview, including the modified Rankin Scale (mRS) and the Glasgow Outcome Scale Extended (GOSE). Face-to-face meetings will be performed at 6 and 24-months, and include reports on outcome from several sources of information: clinician-reported: mRS, GOSE; patient-reported: EuroQol-5 Dimensions-5 Level responses version (EQ-5D-5L), Life satisfaction, Two Simple Questions; observer-reported: Informant Questionnaire on Cognitive Decline in the Elderly-Cardiac Arrest version (IQCODE-CA) and neurocognitive performance measures: Montreal Cognitive Assessment, (MoCA), Symbol Digit Modalities Test (SDMT). Exploratory analyses will be performed with an emphasis on brain injury in the survivors, where the two intervention groups will be compared for potential differences in neuro-cognitive function (MoCA, SDMT) and societal participation (GOSE). Strategies to increase inter-rater reliability and decrease missing data are described. DISCUSSION: The TTM2-trial follow-up is a pragmatic yet detailed pre-planned and standardised assessment of patient's outcome designed to ensure data-quality, decrease missing data and provide optimal conditions to investigate clinically relevant effects of TTM, including OHCA-survivors' neurocognitive function and societal participation.
Keywords: Reproducibility of Results; senioři; Aged; Cardiac arrest; Out-of-Hospital Cardiac Arrest; lidé; Treatment Outcome; Hypothermia; Humans; hypotermie; Randomized Controlled Trials as Topic; Patient Reported Outcome Measures; randomizované kontrolované studie jako téma; Treatment outcome; Multicenter Studies as Topic; Cognitive function; Quality of life; reprodukovatelnost výsledků; multicentrické studie jako téma; výsledek terapie; následné studie; terapeutická hypotermie; Hypothermia, Induced; Follow-Up Studies; zástava srdce mimo nemocnici